THE EFFECT OF PROBLEM-BASED LEARNING MODEL IN CURRICULUM 2013 TOWARDS THE STUDENTS LEARNING OUTCOMES ON LINEAR MOTION TOPIC IN GRADE X SMAN 2 KISARAN A.Y 2014/2015 - Rofi Anggriani; Alkhafi Maas Siregar (UNIVERSITAS NEGERI MEDAN, 2016)
ABSTRACT The aim of this research was known the effect of problem based learning model in Curriculum 2013 towards students’ learning outcomes on topic Linear Motion in Grade X-MIA SMAN 2 Kisaran.Research method was quasi-experiment. The population were all of students in grade X-MIA SMAN 2Kisaran, that consist of 7 classes. The sample of this research was taken by purposive sampling technique.The class X MIA-4 as experimental class used problem based learning model consist of 36 students, and class X MIA-5 as control class used conventional learning consist of 33 students. Instruments that used in this research were non-test(questionnaire) and test instrument.Then data that obtained from the questionnaire analyzed by tabulating using Microsoft excel. The result from the questionnaire (done by the teacher) has good standard. It has the average value from meeting I until meeting III have 90.67. While the data that got from the test instrument was analyzed by t-test statistical analysis. Based on research result using Problem based-learning model thatfocuson planning, learningprocess andevaluation design shown that there were significant enhancementin experimental class.The results that were obtained: pre-test mean value of experiment class was 35.56 and 31.21 for control class and then post-test mean value of the experiment class was 58.89and 38.79 was the mean value for control class.It can be concludedthat the student’s learning outcomes using problem based learning model greater than conventional learning on Linear Motion topic in grade X-MIA SMA N 2Kisaran. Key word: Problem-Based Learning Model, Students’ Learning Outcome, Physic